Nudge Concept and its Controversy - The Behavioural Economics Applications - Masyhuri, Muhammad (PT. Riset Press International, 2023)
Over the decades, the nudge idea of behavioural economics (BE), disseminated by Thaler & Sunstein (2008) in their well-known book, has generated controversial views among many academics and scientists around the world. As an application area of behavioural economics (BE), nudge theory and the nudge concept has found many supporters, but at the same time has generated controversial views among many academics and scholars around the world, especially with regard to its broad definition, decision-making architectures, and libertarian paternalism concepts. Interestingly, this concept has attracted a lot of attention from key government officials, especially in the UK and the US, to change the behaviour of the population to a significant extent. The aim of this study is to discuss the nudge concept and its application to current situations and also to shed light on the critical views of this concept. It was found that this concept, although it has many critics, is considered a useful tool to change the behaviour of people or customers without using coercive measures to achieve the desired result.